Public Education and Income Distribution: A Dynamic Quantitative Evaluation of Education-Finance Reform - Fernández, Raquel; Rogerson, Richard (American Economic Review, 1998)
Many states are implementing school-finance reforms which will have complex effects on income distribution, intergenerational income mobility, and welfare. This paper analyzes the static and dynamic effects of such reforms by constructing a dynamic general equilibrium model of public-education provision and calibrating it using U.S. data. We examine the consequences of a reform of a locally financed system to a state-financed system which equalizes expenditures per student across districts. We find that this policy increases both average income and the share of income spent on education. Steady-state welfare increases by 3.2 percent of steady-state income.